Beyond greed, fear and the iron curtain - Durand, Robert; Simon, M. (Routledge Taylor & Francis Group, 2008)
We examine 13 of the new markets of Eastern Europe from the time of their inception to the end of 2001. In six of those markets – Hungary, Poland, the Czech Republic, Slovenia, Russia and Estonia – we find behaviour consistent with investors following ‘quasi-rational’ strategies in the years following market inception. The results are robust to the suggestion that they are driven by market microstructure. The heuristically driven price behaviour diminishes as these markets mature and is replaced by an increasing association with market movements in major financial centres. We suggest that we have captured the way investors in new markets learn to invest.